Imperforate Anus and Rectourethral Fistula in a Female - Hira Ahmad; Devin R. Halleran; Daniel Dajusta; Katherine McCracken; Marc A. Levitt; Richard J. Wood (Georg Thieme Verlag KG, 2019)
Anorectal malformations (ARM) are complex, heterogeneous disorders and in females the most common anomaly is imperforate anus with a rectovestibular fistula. We describe a malformation not previously encountered in the literature: imperforate anus associated with a normal urethra, normal vagina, but with a recto urethral fistula. Rectourethral fistula in a female is an extremely rare ARM. Precise workup is required to clarify the anatomy for operative planning.